The Influence of Canva Media on Creative Thinking Skills in Science Learning Materials for Grade IV Students of UPTD SD Negeri 122399 - Malau, Elvionita; Simamora, Aprido; Siagian, Asister Fernando; Siagian, Gunaria (Lembaga Riset Mutiara Akbar, 2025)
The low creative thinking ability of students is caused by several factors including inadequate teaching materials and learning media that do not involve students because they use less varied learning models. This study aims to determine the Effect of Canva Media on Creative Thinking Ability in Science Learning Materials for Grade IV Students of UPTD SD Negeri 122399. The type of research used in this study is quantitative research. The research design used is experimental, with a pre-experimental design form that uses a